Finance, Growth and Democracy: Connections and Challenges in Europe and Latin America in the Era of Permacrisis
IX, 370 p. 35 illus.
Keywords: The present volume uses a comparative regional approach to analyze how permacrisis—an extended period of instability and insecurity—has been experienced and dealt with in the European Union (EU) and Latin America. Written by academicians and policy experts from both regions, the volume has three main objectives. Firstly, it critically evaluates the response of regional organizations and governments in the EU and Latin America to the crises that have shaken these regions in recent years. Secondly, chapters contribute to a better understanding of the promised benefits and risks of digital currencies and fintech more generally to economic growth, financial stability and inclusion. Finally, the volume promotes an understanding of the challenges of permacrisis in both the EU and Latin America, as well as encouraging their cooperation at the multilateral and bi-regional levels. Providing an interdisciplinary perspective, this volume will be of interest to researchers and students of international relations, international political economy, international finance and economics, international law, global governance, and regionalism, as well as public officials of ministries of foreign affairs, finance and the economy, public officials of international and regional organizations. This is an open access book.